Input modification in the teaching of english language among federal university lecturers in South-West, Nigeria (2020)
This study investigated input modification in the teaching of English Language among federal university lecturers in South-West, Nigeria. The study examined English grammar and phonology classes. The study made use of Descriptive survey design. The population of the study comprised undergraduate English Language lecturers and their students in South-West, Nigeria. Purposive sampling technique was used to select fifteen (15) English Language lecturers taking English Grammar and phonolo'gy and 350 students in South-West, Federal Universities in Nigeria. Three research questions were answered. Data were collected using Lecturer Classroom Interaction Sheet (LCIS) with reliability co-efficient of 0.76 and Students’ Rating of English Language Lecturer Input Modification (SRELLIM) with reliability co-efficient of 0.82. Data was analyzed using descriptive statistics and T-test. The result of the lecturers’ input simplification practices revealed that lecturer explaining new vocabulary is the most frequently used (27%). This is followed by lecturer using basic vocabulary that matches learners’ language and lecturer explaining an idea using more than one word which have the same proportion of 26.1%. The study also revealed that elaborating self-utterance to make the meaning clear is the most (54.6%) frequently used input elaboration pattern. This is followed by modifying learners’ utterance which amounts to a percentage of 17.0%. The study further revealed a significant difference in score between the two groups of lecturers with t (87) = .00, p < .05, two-tailed where experienced lecturers with (M = 104.33, SD = 24.68) scoring higher than inexperienced lecturers (M = 81.15, SD = 15.58). Also, there was a significant difference in score between the two groups of lecturers with t (348) = .00, p < .05, two-tailed where Ph. D holders (M - 104.33, SD =24.68) scoring higher than MA holders (M = 81.15, SD = 15.58). The study then recommends that Lecturers should be able to use a variety of input modification patterns and adapt the specific patterns that suit the learners they are teaching